2019
DOI: 10.1007/s40430-019-1956-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crack tip shape on near-tip deformation and fields in plastically compressible solids

Abstract: In the present study, the crack tip shape effect on near-tip deformation and fields is numerically investigated for a mode I crack under plane strain and small-scale yielding conditions. We explore here the quasi-static deformations of solids characterized by finite strain elastic-viscoplastic material model with bilinear hardening and hardening-softening-hardening hardness functions. For comparative analyses, both plastically incompressible and plastically compressible solids have been considered. It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 30 publications
(56 reference statements)
3
8
0
Order By: Relevance
“…Furthermore, Rozumek et al (2006) studied the influence of crack-tip curvature on fatigue crack growth experimentally for steel and aluminum, and they observed higher fatigue crack growth for a blunter notch. In the study of Alam et al (2019), similar observations were also revealed. To find out the root cause of this bizarre observation, complete evolution of the near-tip stress-strain field is necessary, however, in the works of Rozumek et al (2006) and Alam et al (2019), the same was not discussed in detail.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Furthermore, Rozumek et al (2006) studied the influence of crack-tip curvature on fatigue crack growth experimentally for steel and aluminum, and they observed higher fatigue crack growth for a blunter notch. In the study of Alam et al (2019), similar observations were also revealed. To find out the root cause of this bizarre observation, complete evolution of the near-tip stress-strain field is necessary, however, in the works of Rozumek et al (2006) and Alam et al (2019), the same was not discussed in detail.…”
Section: Introductionsupporting
confidence: 75%
“…In the study of Alam et al (2019), similar observations were also revealed. To find out the root cause of this bizarre observation, complete evolution of the near-tip stress-strain field is necessary, however, in the works of Rozumek et al (2006) and Alam et al (2019), the same was not discussed in detail. The crack-tip deformation and stress field studies are not only fundamental for understanding of the crack propagation but also for satisfactory development of predictive tools.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…al. [6] investigated the impact of crack tip shape on the deformation and fracture of plastically compressible materials under monotonic loading.…”
Section: Introduction *mentioning
confidence: 99%